Police Integrity and the Code of Silence (CoS): Evidence from a Large-Scale Scenario-Based Survey in Indonesia - -, Dr. Indarto, S.H., S.Sos., S.I.K., M.Si (UI Scholars Hub, 2026)
Issues of police integrity are not only driven by individual misconduct but are also sustained by organizational norms that inhibit the reporting of wrongdoing, known as the Code of Silence (CoS). This article reports the results of a large-scale, scenario-based police integrity survey conducted among personnel of the Indonesian National Police (Polri). After excluding responses that did not meet the honesty criterion, analyses were conducted on 57,574 respondents. Respondents evaluated six misconduct scenarios and assessed perceived seriousness, perceived deterrence (likelihood of detection and sanction), knowledge of rules, and willingness to report. Reliability tests indicated very strong internal consistency (Cronbach’s α = 0.913–0.973). The results show that drunk driving is consistently rated as the most serious misconduct and the most reportable. In contrast, receiving gratuities and other forms of minor misconduct are rated as least serious and least likely to be reported. Perceptions vary significantly by assignment type (staff vs. operational), years of service, and rank, indicating differences in how integrity expectations are interpreted within the organization. In addition, Polri personnel tend to estimate that the public rates some forms of misconduct as less serious than internal ratings, suggesting a misalignment between internal norms and public expectations. These findings highlight the importance of increasing the certainty of sanctions, strengthening confidential reporting mechanisms, and designing integrity interventions tailored to units and career stages where the CoS is most entrenched.